2006
DOI: 10.1002/adma.200600021
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanofibers Uniformly Grown on γ‐Alumina Washcoated Cordierite Monoliths

Abstract: A uniform layer of carbon nanofibers is grown on a cordierite monolith by first coating the monolith with a thin layer of γ‐alumina. The nanofibers form a thick, uniform layer on the monolith walls as shown in the figure, leading to the formation of a mesoporous and mechanically robust composite. The absence of microporosity in the composite and the ability to tune the thickness of the nanofiber layer suggests that these nanofibers/monolith composites may be useful as catalyst supports for liquid‐phase catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 11 publications
1
55
1
Order By: Relevance
“…Also, a larger nickel particle size resulted in nanofiber growth outside of the monolith. To enable a better growth rate and uniform distribution of nanofibers, García-Bordeje' et al have suggested using a thin γ-alumina washcoating of approximately 0.1 µm [104,201].…”
Section: Coating Carbon Materials Onto Monolithsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a larger nickel particle size resulted in nanofiber growth outside of the monolith. To enable a better growth rate and uniform distribution of nanofibers, García-Bordeje' et al have suggested using a thin γ-alumina washcoating of approximately 0.1 µm [104,201].…”
Section: Coating Carbon Materials Onto Monolithsmentioning
confidence: 99%
“…It was concluded that sols prepared via pseudoboehmite with urea and nitric acid and hydrolysis of tri-sec-butoxide are most suitable for sol-gel alumina coating of monoliths [10]. A typical sol-gel method of coating involves dipping the monolith in a sol from pseudoboehmite, urea and 0.3 M nitric acid in a weight ratio of 2:1:5, followed by emptying the channels, drying and finally calcination [104]. Sol-gel coating may be advantageous over conventional colloidal coating of monoliths, due to a strong adherence to the monolith, as the alumina layer forms on the surface of the channels.…”
Section: Sol-gelmentioning
confidence: 99%
“…CNF were formed under a gas flow of ethane and hydrogen (50:50). The detailed preparation method is described elsewhere [40]. The specific monolith used for the experiments here described had a diameter of 22 mm and a height of 60 mm, with square channels of 1 mm diameter.…”
Section: Experimental Materials and Chemicalsmentioning
confidence: 99%
“…The growth of CNF on the surface of a ceramic monolith has already been reported in the literature [39,40], as well as the application of the system to catalysis, including catalytic ozonation [22,39].…”
mentioning
confidence: 99%
“…In particular, the use of powdery CNFs leads to agglomeration problems and difficulty of filtration in slurry phase operation, and pressure drop in gas phase operation. These inconveniences can be prevented by the incorporation of carbon filaments into larger objects like, for example, ceramic monoliths [7,8], sintered metal fibres or a carbon felt [9]. Another alternative could be the development of membranes consisting of entangled carbon nanofibers of a few tens of nanometer diameter obtained by electrospinning of a polymer followed by pyrolysis at high temperature [10,11].…”
Section: Introductionmentioning
confidence: 99%